Audiodeskriptionsübersetzung als alternative Methode der Filmbeschreibung - Korycińska-Wegner, Małgorzata (Studia Germanica Posnaniensia, 2014)
This paper discusses the method of audio description as intralingustic and interlinguistic translation. It offers a contrastive analysis of the audio described scripts of the film Imagine of Andrzej Jakimowski in German and Polish, with a view on some of challenges that could arise when translating this type of text. After informations about creation of audio description and introduction of research in the field of the translation of existing audio descriptions, the paper suggests that similar conventions have evolved in German and Polish regarding both the content and expressions of ADs. These similarities are illustrated with reference to the German and Polish ADs for Imagine, which are analysed on the example of main characters and action places.